IB-DFE with interference alignment precoding scheme for MC-CDMA systems - Moreira, José Eduardo Leal (2013)
To achieve high bit rates, needed to meet the quality of service requirements of future multimedia applications, multi-carrier code division multiple access (MC-CDMA) has been considered as a candidate air-interface. Interference alignment (IA) is a promising technique that allows high capacity gains in interfering channels. On the other hand, iterative block decision feedback equalization (IB-DFE) based receivers can efficiently exploit the inherent space-frequency diversity of the MIMO MC-CDMA systems. In this thesis we proposed an IA precoding at the transmitter with IB-DFE based processing at the receiver for MC-CDMA systems. The IA precoding is applied at chip level instead of the data symbols level, as in the conventional IA based systems. The receiver is designed in two steps: first the equalizers based on zero forcing (ZF) or minimum mean square error (MMSE) are used to remove the aligned users´ interference. Then and after a whitening noise process, an IB-DFE based equalizer is designed to remove both the residual inter-user aligned and inter-carrier interferences. The results have shown that the obtained performance is very close to the one obtained by the optimal matched filter, with few iterations at the receiver side.